2022
DOI: 10.14341/probl12892
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thyrotropin - indicatior of monitoring of iodine deficiency severity. What’s level is considered a «cutoff point»?

Abstract: BACKGROUND: The issues of monitoring the effectiveness of iodine deficiency prevention programs are an important component in the process of iodine elimination. Neonatal thyrotropin (TSH) has been used as a criterion for the severity of iodine deficiency since 1994, however, the question of the “cut-off point” of the neonatal TSH level has been widely discussed in the recent literature.AIM: Evaluate the criterion for neonatal hyperthyroidism above 5 mIU/l from the perspective of monitoring iodine deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
1
1
Order By: Relevance
“…11 Although the WHO establishes a cut-off point of nTSH levels at 5 mIU/L to differentiate adequate and deficient iodine levels in a population, 1 a study that assessed pregnant women with adequate iodine levels and TSH levels in their newborn infants reported that the cut-off point for nTSH should be 2.77 mIU/L, lower than what has been proposed by the WHO. 25 Regardless of the cut-off point used, the prevalence of nTSH levels ≥ 5 mIU/L in our study was 9.6%, which suggests the presence of mild ID in the population of La Pampa. Although this study did not cover other indicators of ID, the percentage of nTSH ≥ 5 mIU/L mentioned above emphasizes the need for continuous monitoring of iodine nutritional status in the population, as even the presence of mild ID may result in significant damage to the neurodevelopment and other aspects of child health.…”
Section: Discussioncontrasting
confidence: 54%
“…11 Although the WHO establishes a cut-off point of nTSH levels at 5 mIU/L to differentiate adequate and deficient iodine levels in a population, 1 a study that assessed pregnant women with adequate iodine levels and TSH levels in their newborn infants reported that the cut-off point for nTSH should be 2.77 mIU/L, lower than what has been proposed by the WHO. 25 Regardless of the cut-off point used, the prevalence of nTSH levels ≥ 5 mIU/L in our study was 9.6%, which suggests the presence of mild ID in the population of La Pampa. Although this study did not cover other indicators of ID, the percentage of nTSH ≥ 5 mIU/L mentioned above emphasizes the need for continuous monitoring of iodine nutritional status in the population, as even the presence of mild ID may result in significant damage to the neurodevelopment and other aspects of child health.…”
Section: Discussioncontrasting
confidence: 54%
“…11 Pese a que la OMS establece un punto de corte de TSHn de 5 mUI/l para diferenciar estados de suficiencia o DI en una población, 1 un estudio que evaluó a embarazadas yodosuficientes y las TSH de sus RN plantea que el punto de corte de TSHn debería ser de 2,77 mUI/l, un valor menor al propuesto por la OMS. 25 Independientemente del punto de corte considerado, la prevalencia de TSHn ≥5 mUI/l del 9,6 % encontrada en este estudio sugiere la presencia de una DI leve en la población de La Pampa. Aunque este estudio no abarca otros indicadores de DI, el mencionado porcentaje de TSHn ≥5 mUI/l enfatiza la necesidad de un monitoreo continuo del estado nutricional de yodo en la población, ya que incluso la presencia de una DI leve puede producir daños significativos en el neurodesarrollo y otros aspectos de la salud infantil.…”
Section: Discussionunclassified